1987
DOI: 10.5144/0256-4947.1987.319
|View full text |Cite
|
Sign up to set email alerts
|

Acute Viral Hepatitis in Hummayat Infectious Diseases Hospital, Baghdad

Abstract: Acute viral hepatitis occupies an important place among infectious diseases in the Baghdad area and was responsible for 11.2% of the total admissions to Hummayat Infectious Diseases Hospital, Baghdad, over the five-year period 1979 to 1983. There was no change in the admission rate during this five-year period, while there was a regular and significant increase during the last six months of each year. The total number of males admitted was higher than females (P <0.01), while the fatality rate was higher in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…Several authors working in the Middle East and India reported a worse prognosis for pregnant women with hepatitis [12][13][14] in contrast to the experience in western Europe [15,16]. We have reported a higher mortality in Iraqi females of childbearing age [17] and our results suggested that it is the female sex and not pregnancy that is responsible for the higher mortality in females of this age group. However, larger series should be studied to clarify this point.…”
Section: Discussioncontrasting
confidence: 55%
“…Several authors working in the Middle East and India reported a worse prognosis for pregnant women with hepatitis [12][13][14] in contrast to the experience in western Europe [15,16]. We have reported a higher mortality in Iraqi females of childbearing age [17] and our results suggested that it is the female sex and not pregnancy that is responsible for the higher mortality in females of this age group. However, larger series should be studied to clarify this point.…”
Section: Discussioncontrasting
confidence: 55%